Biliverdin incorporation into the cyanobacteriochrome SPI1085g3 from Spirulina - Wu, Xian-Jun; Qu, Jia-Ying; Wang, Chang-Tian; Zhang, Ya-Ping; Li, Ping-Ping (Frontiers in Microbiology, 2022)
Cyanobacteriochromes (CBCRs) bind linear tetrapyrrole chromophores, mostly phycocyanobilin (PCB), and exhibit considerable spectral diversity with high potential for biotechnological applications. Particular attention has been given to the conversion into intrinsic biliverdin (BV) incorporation due to the absence of PCB in mammalian cells. Our recent study discovered that a red/green CBCR of Spirulina subsalsa, SPI1085g3, covalently attached to PCB and exhibited strong red fluorescence with a unique red/dark switch. Here, we found that SPI1085g3 could be modestly chromophorylated with BV and absorb somewhat redshifted (10 nm) red light, while the single C448S mutant could efficiently bind BV and exhibited unidirectional photoconversion and moderate dark reversion. The fluorescence in its dark-adapted state was switched off by red light, followed by a moderate recovery in the dark, which were properties similar to those of PCB-binding SPI1085g3. Furthermore, by introducing the CY motif into the conserved CH motif for chromophore attachment, we developed another variant, C448S_CY, which showed increased BV-binding efficiency. As expected, C448S_CY had a significant enhancement in fluorescence quantum yield, reaching that of PCB-binding SPI1085g3 (0.14). These BV-binding CBCRs offer an improved platform for the development of unique photoswitchable fluorescent proteins compared with PCB-binding CBCRs.